Nigella sativa fixed and essential oil supplementation modulates hyperglycemia and allied complications in streptozotocin-induced diabetes mellitus - Sultan, Muhammad Tauseef; Butt, Masood Sadiq; Karim, Roselina; Zia-Ul-Haq, Muhammad; Batool, Rizwana; Ahmad, Shakeel; Aliberti, Luigi; De Feo, Vincenzo (Hindawi Publishing Corporation, 2014)
In the recent era, diabetes mellitus has emerged as one of the significant threats to public health and this situation demands the attention of the researchers and allied stakeholders. Dietary regimens using functional and nutraceutical foods are gaining wide range of acceptance and some traditional medicinal plants are of considerable importance. The main objective of this instant study was to explore the antidiabetic potential of Nigella sativa fixed oil (NSFO) and essential oil (NSEO). Three experimental groups of rats received diets during the entire study duration, that is, D1 (control), D2 (NSFO: 4.0%), and D3 (NSEO: 0.30%). Experimental diets (NSFO & NSEO) modulated the lipid profile, while decreasing the antioxidant damage. However, production of free radicals, that is, MDA, and conjugated dienes increased by 59.00 and 33.63%, respectively, in control. On the contrary, NSFO and NSEO reduced the MDA levels by 11.54 and 26.86% and the conjugated dienes levels by 32.53 and 38.39%, respectively. N. sativa oils improved the health and showed some promising anti-diabetic results.